2013
DOI: 10.1186/1471-2431-13-11
|View full text |Cite
|
Sign up to set email alerts
|

Type D personality is a risk factor for psychosomatic symptoms and musculoskeletal pain among adolescents: a cross-sectional study of a large population-based cohort of Swedish adolescents

Abstract: BackgroundType D personality, or the “distressed personality”, is a psychosocial factor associated with negative health outcomes, although its impact in younger populations is unclear. The purpose of this study was to investigate the prevalence of Type D personality and the associations between Type D personality and psychosomatic symptoms and musculoskeletal pain among adolescences.MethodsA population-based, self-reported cross-sectional study conducted in Västmanland, Sweden with a cohort of 5012 students in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 45 publications
4
21
1
5
Order By: Relevance
“…It also made sense that this negative lens would be more relevant to psychological symptoms, which are arguably less constrained by the external world than physical symptoms. These results are also consistent with previous research that found Type D to be associated with higher rates of musculoskeletal pain and psychological symptom reporting (Condén et al, 2013). It may be that as the rate of negative affectivity and social inhibition increases, so does the subjective experience of illness and illness-related symptoms.…”
Section: Type D and Health Outcomessupporting
confidence: 82%
See 1 more Smart Citation
“…It also made sense that this negative lens would be more relevant to psychological symptoms, which are arguably less constrained by the external world than physical symptoms. These results are also consistent with previous research that found Type D to be associated with higher rates of musculoskeletal pain and psychological symptom reporting (Condén et al, 2013). It may be that as the rate of negative affectivity and social inhibition increases, so does the subjective experience of illness and illness-related symptoms.…”
Section: Type D and Health Outcomessupporting
confidence: 82%
“…In a sample of over 3000 cancer survivors, Mols et al (2012) found that Type D patients reported significantly higher levels of general somatic symptoms, sleep disturbance, pain, and fatigue. Similarly, in a recent population survey of more than 5000 Swedish adolescents, Type D was associated with higher levels of self-reported psychosomatic symptoms, musculoskeletal pain, and sleep disturbance (Condén, Leppert, Ekselius, & Åslund, 2013;Condén, Rosenblad, Ekselius, & Aslund, 2014). Other somatic research has found that negative affectivity and social inhibition are also each independently associated with increased somatization and unexplained symptoms (Watson & Pennebaker, 1989;Wongpakaran & Wongpakaran, 2014).…”
Section: Type D Personality and Health Outcomesmentioning
confidence: 99%
“…These findings in general population coincide with the previous cross-sectional study in the United Kingdom (Williams et al, 2015). This personality type has been associated with a poorer physical health status (Versteeg et al, 2012), musculoskeletal pain and psychosomatic symptoms (Conden et al, 2013). It is counterfactual that people with Type D personality report worse lifestyle or health perceptions, but on the other hand the sample of people with cardiovascular diseases report similar Type D features to general population.…”
Section: Discussionsupporting
confidence: 75%
“…Whereas, the prevalence of Type D personality among non-clinical samples is various, but generally considered to be lower than in patients. In the general population the prevalence of this personality type ranges from 13% (Conden, Leppert, Ekselius, & Åslund, 2013) to 40% (Horwood, Chamravi, & Tooley, 2015). Type D personality is described as a negative factor due to associations with poorer physical and mental health (Mols & Denollet, 2010), higher incidence of adverse clinical outcomes (Pedersen & Denollet, 2006) and lower scores of health-related quality of life (Staniute et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The Type D personality has also been negatively associated with mental and physical well‐being and health‐promoting behavior in non‐cardiovascular patients and in the general population (Gangwisch, Malaspina, Babiss et al ., ; Gilmour & Williams, ; Mols & Denollet, , ; Williams, O'Connor, Grubb & O'Carroll, ). Studies have shown that Type D personality is associated with psychosomatic symptoms, musculoskeletal pain, and sleep problems, even among adolescents (Conden, Ekselius & Aslund, ; Conden, Leppert, Ekselius & Aslund, ).…”
Section: Introductionmentioning
confidence: 99%